2018
DOI: 10.1016/j.ssci.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The application of system dynamics modelling to system safety improvement: Present use and future potential

Abstract: System Dynamics has the potential to study the aspects of complex systems including its likely effect of modifications to structural and dynamic system properties that cannot be achieved with traditional approaches. This paper presents a review of literature addressing safety issues using system dynamics across safety-critical domains. Forty studies were included and classified based on a customised human factors safety taxonomy framework. The thematic analysis of the literature resulted in five themes: extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 77 publications
0
8
0
1
Order By: Relevance
“…Various studies have demonstrated the capability and fitness of SD in improving the understanding of complex safety systems. Thus, it has been widely used in the safety research to understand the contributing factors of accidents (Ibrahim Shire et al. , 2018; Shin et al.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have demonstrated the capability and fitness of SD in improving the understanding of complex safety systems. Thus, it has been widely used in the safety research to understand the contributing factors of accidents (Ibrahim Shire et al. , 2018; Shin et al.…”
Section: Methodsmentioning
confidence: 99%
“…From several possible configurations, at least the combination of EAST and STAMP has been described (Salmon et al, 2018), as well as a combination of network metrics and FRAM (Falegnami et al, 2020). We would also like to point to the fact that we only applied a selection of methods for this study, but ideally future research would draw a full comparison of strengths and weaknesses of several other available systemic methods, such as CWA (Naikar, 2017), system dynamics (Ibrahim Shire et al, 2018), or Net‐HARMS (Hulme et al, 2021; 2021) to just name a few. During the writing of this manuscript, one publication in particular deserves attention, because it compares the reliability and validity of, STPA and the EAST broken‐links approach (Hulme et al, 2021), with the recommendation to further test extensions to enhance the reliability and validity of these methods in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Much has been written regarding the value of techniques such as ABMS in studying processes over time or comparing competing models or sets of rules and parameters (e.g., Hughes et al 2012, Ibrahim Shire, Jun, and Robinson 2018, Smaldino, Calanchini, and Pickett 2015. These enable the study of dynamic processes, non-linear relationships, and phenomena at different levels of abstraction (e.g., Hughes et al 2012.…”
Section: Improving Model Building In Ergonomics Theorisationmentioning
confidence: 99%